Differencirovannyj podchod k ispol'zovaniju fiziceskich sredst vosstanovlenija - Jakimenko, S. N. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The purpose of the research - the development of a differentiated approach to the use of physical means of restoration at the stage of precompetitive training of highly skilled sportsmen of acyclic kinds of sports.